Challenges of Speaking English in Chemistry Seminars: A Student Survey - Nuha Fauziyah; Wahyunengsih; Nisrina Auliya (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2026)
The ability to speak English effectively in chemistry seminars is an important skill for student, as their activities require clear and academic delivery of scientific concepts. This study aims to identify and measure the types of challenges students face when speaking English in chemistry seminars. This study used a quantitative descriptive research design with a survey method. The research instrument was a closed-ended questionnaire using a five-point Likert scale to forty-one Chemistry students. The questionnaire covered four main aspects: linguistic challenges, psychological factors, and academic difficulties. Data were analyzed descriptively using frequencies, percentages, and average scores to determine the level of dominance of each type of challenge. The study findings indicate that linguistic challenges, particularly difficulty finding appropriate chemical vocabulary when speaking, frequent nervousness when speaking in English in chemistry seminars, frequent difficulty constructing spontaneous sentences when explaining chemical concepts, limited scientific vocabulary, and difficulty constructing academic sentences. And linguistic factors, particularly difficulty pronouncing chemical terms in English correctly, not being very proficient in using scientific terms in oral contexts, and difficulty using conjunctions or connectors when explaining chemical ideas, were the most dominant obstacles.